The Role of Electronic Periodontal Probing in Preventing the COVID-19 Transmission in Dentistry - Darius-Valentin Sandu; Ionuț Luchian; Irina Șufaru; Giorgio Nichitean; Ancuța Goriuc; Alexandra Mârțu; Sorina Solomon (Elsevier, 2021)
Aim or Purpose: The current pandemic context requires a series of preventive measures to reduce the risk of contamination during dental care procedures.One of the most effective is to reduce the clinical working time (CWT) but without influencing the quality of the treatments. Materials and Methods: The present study was performed on a group of 27 students from the Faculty of Dental Medicine-Grigore T. Popa University of Medicine and Pharmacy Iasi-Romania, during the 1st of February and the 31st of March 2021. All patients underwent both conventional probing (CP) and electronic probing (EP).We evaluated the CWT required to perform the periodontal probing procedure and the related periochart. The accuracy of the measurements and the tolerance of the subjects were also evaluated. Results: The mean values for clinical working time in order to perform periodontometry maneuvers were significantly different. (34.20 ± 6.8 min for CP and 11.30 ± 3.3 min for EP).The results of the present study highlighted the fact that the mean CWT was reduced by approximately 300% in the case of the EP compared to the CP without affecting the quality and accuracy of the dental procedure. Our results point that the CWT for EP is minimal related to the exposure time necessary for viral contamination through aerosols. Conclusions: In a pandemic context, EP may represent not only a viable diagnostic tool but also can be successfully associated with the prevention of aerogenic viral transmission through reducing exposure and maintaining a high-quality standard.